Woakes’ Syndrome; Rare Manifestation of Nasal Polyposis: Experience of Seven Patients - Günebakan, Çağlar; Kuzu, Selçuk; Bozkurt, Erhan; Yücedağ, Fatih; Canbek, İhsan (ENT Updates, 2022)
Background: Woakes’ syndrome, first described by Woakes in 1885 which is also bet- ter known as ethmoiditis, is a very uncommon entity of severe nasal polyposis caus-ing disfigured facial appearance. In this study, we aimed to present the diagnosis and management of seven patients’ series with Woakes’ syndrome in the light of currentliterature. Methods: The medical records of seven patients who had functional endoscopic sinussurgery because of nasal polyposis that caused nasal roof deformity between January 2013 and June 2020 in a tertiary hospital otorhinolaryngology department were eval-uated retrospectively. Demographic aspects, examination data, rhinological surgeryhistory, Lund-Mackay scores at admission, surgical procedures performed, and follow- up periods were analyzed. Results: All patients had bilateral severe nasal polyposis and significant nasal boneexpansion. Bilateral functional endoscopic sinus surgery was applied to all patients and additionally septoplasty was applied to one patient and septorhinoplasty to two patients in the same session. Five patients stated they did not want septorhinoplastyin the same session. We tried reduction of nasal bones with a finger pressure in thesepatients. While we achieved a satisfactory reduction in three of these patients, it was unsuccessful in two cases. Conclusion: Treatment of nasal polyps should be achieved by functional endoscopic sinus surgery for Woakes’ syndrome. Topical and systemic treatment of the noseshould slow down or evade the recurrence of the nasal polyps. Approach to nasal deformity should be addressed during the initial surgery if feasible.